Ukraine : Second Review Under the Extended Fund Facility and Requests for Waivers of Non-Observance of Performance Criteria, Rephasing of Access and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Ukraine's Second Review Under the Extended Fund Facility and Requests for Waivers of Nonobservance of Performance Criteria (PCs), Rephasing of Access and Financing Assurances Review. The economy of Ukraine has stabilized and is showing signs of a gradual recovery. Following a severe economic crisis, activity is picking up, inflation has receded quickly, and confidence is improving. International reserves have doubled to more than USD 14 billion. Continued policy implementation is needed to achieve program objectives, given the still significant challenges lying ahead. The IMF staff supports the completion of the second review, and the authorities' requests for waivers of the missed PCs, rephasing of access, and financing assurances review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet